2021
DOI: 10.1080/15440478.2021.1907832
|View full text |Cite
|
Sign up to set email alerts
|

Jute and Luffa Fiber-Reinforced Biocomposites: Effects of Sample Thickness and Fiber/Resin Ratio on Sound Absorption and Transmission Loss Performance

Abstract: The acoustic properties of natural fiber-reinforced composites should be identified before using these materials in various engineering applications including sound and vibration isolation. This study investigates the effects of sample thickness and fiber/resin ratio on the acoustic performance of jute and luffa fiber-reinforced biocomposites. For this purpose, jute and luffa composite samples with different thicknesses and fiber/epoxy ratios are manufactured and their sound absorption coefficients (SACs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In the first stage of the study, a design was made of the three types of filaments (PLA coconut, PLA birch, and PLA) and with the five types of infill density (20%, 40%, 60%, 80% and 100%) in order to characterize the acoustic performance of those three types of materials. Since the sound absorption coefficient is a ratio of reflected to incident sound energy, a value of 0 indicates complete reflection with no absorption [ 53 ]. On the other hand, the value of 1 of the absorption coefficients shows that all the sound energy is absorbed without reflection [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first stage of the study, a design was made of the three types of filaments (PLA coconut, PLA birch, and PLA) and with the five types of infill density (20%, 40%, 60%, 80% and 100%) in order to characterize the acoustic performance of those three types of materials. Since the sound absorption coefficient is a ratio of reflected to incident sound energy, a value of 0 indicates complete reflection with no absorption [ 53 ]. On the other hand, the value of 1 of the absorption coefficients shows that all the sound energy is absorbed without reflection [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since the sound absorption coefficient is a ratio of reflected to incident sound energy, a value of 0 indicates complete reflection with no absorption [ 53 ]. On the other hand, the value of 1 of the absorption coefficients shows that all the sound energy is absorbed without reflection [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it has been reported that higher resin content would fill the pores and voids between the matrix and reinforcement and cause disruption in transmission and reduce noise absorption. 27 Thickness of the samples and amount of air gaps were also found to influence the sound absorption in biocomposites. 28 Creation of air channels between the reinforcing particles for air flow increases the resistivity and hence better sound absorption could be achieved.…”
Section: Changes In the Sound Absorption Coefficient Due To The Addit...mentioning
confidence: 98%
“…Moreover, the properties of 3D printing material are listed in Table S3 (Supporting Information). [27,30,[47][48][49][50][51][52][53]…”
Section: Meta-symbiotic Acoustic Functionmentioning
confidence: 99%